INTERNALISASI KARAKTER TANGGUNG JAWAB MELALUI MODEL PROJECT BASED LEARNING PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI NO.038/XI KOTO LOLO - Agustriwita; Ahmad Zuhdi; Oki Mitra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the internalization of responsibility character through the Project Based Learning (PjBL) model in Islamic Religious Education (PAI) learning at SD Negeri No.038/XI Koto Lolo, Sungai Penuh City. The research is motivated by the dominance of conventional approaches in PAI learning that have not optimized the internalization of responsibility character, some students showed low awareness of group tasks, uneven project task distribution, and limited ability to connect projects with Islamic values. This research employed a descriptive qualitative method with a case study approach. Research informants were the School Principal, Grade V Islamic Religious Education Teacher, and five Grade V students. Data collection used observation, interviews, and documentation techniques, while data analysis included data reduction, data display, and conclusion drawing with source and method triangulation. The results show that the internalization process of responsibility character occurs gradually through six PjBL stages from introducing the concept of responsibility as amanah to experience evaluation, but still faces obstacles including lack of student initiative, uneven task distribution, and unfamiliar self-reflection culture. Forms of internalization encompass three moral dimensions with the moral knowledge dimension showing the best achievement, while moral feeling and action dimensions still need development. Supporting factors include student motivation, teacher competence, school support, and relevant learning design. Inhibiting factors include diverse student motivation, limited technological facilities, limited learning time, and lack of parental support.